Who are the Actors involved and How the Decision Making Process for the Exploitation of University Patents have been made? - Ismail, Kamariah; Mason, Colin; Cooper, Sarah; Wan Omar, Wan Zaidi; Majid, Izaidin (International Business Academics Consortium (IBAC), 2008)
The commercialisation of university patents via licensing to established companies or spin-off formations are the common methods adopted by universities to exploit their patents. This paper looks very closely into who were involved and how the decision-making were made by one university to patent and through which route to exploit its portfolio of patents. This paper is based on a case study of a university in Scotland with 12 patents or inventors were selected. The findings showed that the actors involved in the decision to patent were: inventors, industry and the Technology Transfer Office (TTO), or between two of the above parties. However, the decisions to commercialise via spin-off formations were influenced by factors such as how they recognised the opportunities of their technologies such as through industrial working experiences, and the motivation factors to see their inventions being exploited. On the other hand, for patents those were licensed to established companies, the decisions to exploit through licensing to established companies either came from the decision of the three actors individually or joint decisions between them. The significant difference is that for the patents that were exploited via licensing to established companies, the inventors did not have the motivation to be an entrepreneur, and were not wiling to take risks in a new business venture. The findings also show that, the TTO did not have special due diligence system in helping inventors to identify opportunities. Lack of skills and capabilities, and marketing efforts by the TTO in all sectors resulted in the decisions to form spin-offs that were based on the inventors’ motivation and industrial experience.